QUANTITATIVE SCHLIEREN MEASUREMENT OF 3 DIMENSIONAL TEMPERATURE, CONCENTRATION AND VELOCITY FIELDS IN A GAS FLOW - IFFA, EMISHAW DANDENA IFFA (2011)

(untitled)
Background Oriented Schlieren (BOS) estimates the flow behaviour that exists between the camera and background from the shift in the background image features due to the change in the transfer channel function. The current optical flow techniques used to find the deflection vectors of the change in background images rely on two main assumptions: global constant value of intensity and continuity of local motion. The global intensity invariance assumption hardly works for BOS technique when imaging a self luminous flow. In this thesis, an optical flow equation which takes the change in intensity into account and an estimation motion model that considers both translational and rotational deflections were developed. The results showed that for a transparent gas jet all the tested optical flow algorithms worked well. However the proposed model gave better results for BOS images taken through natural gas flames and smoke from a fog generator. The developed deflection vector estimation algorithm and optical tomography served as a tool to extract the index of refraction of the gaseous fields. The Gladstone-Dale relationship was used to show the direct correlation between the index of refraction and density of the flow. Three different types of axi-symmetric flows were used as gas sample media. These were a CNG injected fuel jet, an open methane flame and a hot air jet. Based on the measured index of refraction the species mole fractions of CNG injected jet and methane flame were measured. In addition, the three dimensional temperature fields of the methane flame and the hot air were also measured and displayed. The other main contribution of this research was the use of Background Oriented Schlieren (BOS) technique for the measurement of the velocity field of a variable density round jet. The density field was further exploited to extract the axial and radial velocity vectors for six different jet-exit temperature values with the aid of the continuity and energy equations. Results of the measured temperature and velocity vector fields were compared with thermocouples and hot wire anemometry readings respectively and showed good agreements.